Analysis of Filipino generation Z’s awareness toward fair trade ethical fashion and the factors related to purchasing behavior of fashion products - Larosa, Jackielyn E.
Despite the awareness of Filipino Generation Z consumers towards ethical fashion, brands need help in exploring this market further with regards to the concept of fair trade and how this relates to their purchasing behaviors. This study aimed to analyze the level of awareness of selected Filipino Generation Z consumers toward fair trade ethical fashion and the factors affecting their purchasing behavior of fashion products. It further determined whether this level of awareness correlates with the different factors of purchasing behavior. Quantitative data was collected through an online survey of 107 working Filipino Generation Z members living in Metro Manila under ages 21 to 28 years old (as of March 2024). They are recruited through non-probability convenience sampling and snowball sampling. A statistical analysis was done to determine the frequencies, percentages, mean, standard deviation, and skewness. The Spearman’s rho with a two-tailed significance test (CI = 0.05) was used to determine correlation between the level of awareness and factors related to purchasing behavior. Filipino Generation Z consumers have an above-average level of awareness of fair trade ethical fashion and prioritize the combination of taste, fit, and quality in their fashion purchases, with price not holding as much importance. The level of awareness of Filipino Generation Z consumers toward fair trade ethical fashion demonstrates a significant relationship with values (personal and moral beliefs) and price as factors influencing their purchasing behavior of fashion products. Additional research with qualitative data through focus group discussions can be conducted to be able to get a more in depth understanding of the results. It is also recommended to study local brands’ perspectives on fair trade ethical fashion, to provide another layer of understanding within the local ethical fashion industry.